2018
DOI: 10.5005/jp-journals-10024-2218
|View full text |Cite
|
Sign up to set email alerts
|

Clinicomicrobiological Evaluation of 2% Chitosan Mouthwashes on Dental Plaque

Abstract: Aim: This study was conducted to evaluate microbiological and clinical effects of a chitosan chlorhexidine (CH) mouthrinse on plaque control. Materials and methods:Subjects were divided into three groups. Group I included 15 subjects who used 0.2% chlorhexidine digluconate (CHX), group II included 15 subjects who used 2% chitosan (CH) solution, and group III involves 15 subjects who used 0.2% chlorhexidine/2% CH combination. Plaque index (PI), gingival index (GI), and probing depth (PD) were recorded at the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“… (1) Surfactant (may act as a solubiliser, emulsifier, emulsion stabiliser, detergent, wetting agent, foaming agent/defoamer and may possess antimicrobial features) [ 75 ]; (2) mucoadhesive film former (filmogenic agents) (it is suggested that they may act as a moisturiser, as dressing for wounds, to prevent dental plaque and stain formation, to prevent demineralisation, as a barrier to relieve pain in oral lesions such as aphthous ulcers, to improving the delivery and retention of actives) [ 27 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 ]; (3) remineralisation agent (to remineralise the demineralised tooth surface in dental caries or erosion as well as to prevent demineralisation, also in dentin hypersensitivity to obturate the dentinal tubules); (4) antimicrobial agent (an oral antiseptic, it may act as a preservative); (^) means it is discussed in the subsequent text. …”
Section: Tablementioning
confidence: 99%
“… (1) Surfactant (may act as a solubiliser, emulsifier, emulsion stabiliser, detergent, wetting agent, foaming agent/defoamer and may possess antimicrobial features) [ 75 ]; (2) mucoadhesive film former (filmogenic agents) (it is suggested that they may act as a moisturiser, as dressing for wounds, to prevent dental plaque and stain formation, to prevent demineralisation, as a barrier to relieve pain in oral lesions such as aphthous ulcers, to improving the delivery and retention of actives) [ 27 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 ]; (3) remineralisation agent (to remineralise the demineralised tooth surface in dental caries or erosion as well as to prevent demineralisation, also in dentin hypersensitivity to obturate the dentinal tubules); (4) antimicrobial agent (an oral antiseptic, it may act as a preservative); (^) means it is discussed in the subsequent text. …”
Section: Tablementioning
confidence: 99%
“…In Figures 2, 3, the review authors' judgments on each RoB-2 were shown as percentages across all included research, and the RoB-2 for each included study was presented as a summary. Among the three included studies, one study had low risk of bias [20] and two other studies has high over all risk of bias [21,22].…”
Section: Table 1: Summation Table Of the Included Studiesmentioning
confidence: 99%
“…al., namun penelitian ini menggunakan konsentrasi obat kumur chitosan yang berbeda yaitu 1% dan chitosan berat molekul tinggi yang larut asam. 33 Berat molekul chitosan yang digunakan dalam penelitian ini memiliki batasan yang tidak jelas antara satu dengan yang lainnya sehingga memberikan hasil yang masih inkonsisten. Penelitian selanjutnya diharapkan dapat memberikan hasil yang lebih konsisten.…”
Section: Pembahasanunclassified